Conditional effects of mindfulness on sleep quality among clinical nurses: the moderating roles of extraversion and neuroticism. Issue 4 (21st April 2019) - Fang, Yueyan; Kang, Xiaofei; Feng, Xiujuan; Zhao, Di; Song, Donghua; Li, Ping
ABSTRACT: The present study aimed to examine the potential moderating role of personality traits in the psychological mechanisms by which mindfulness can lead to better sleep quality. A total of 172 oncology nurses participated in this study, and completed self-reported measures, including the Mindful Attention Awareness Scale (MAAS), Pittsburgh Sleep Quality Index (PSQI), and 44-item Big Five Inventory (BFI-44). Results showed that mindfulness was correlated with the global PSQI score ( r  = −0.281, p  < 0.01).Trait extraversion and neuroticism moderated the mindfulness-sleep relationship. The simple slope analysis indicated that the negative relationship between mindfulness and the global PSQI score was only significant at higher levels of extraversion (β = −0.419, p  < 0.001) and lower levels of neuroticism (β = −0.344, p  = 0.001). Additionally, the Johnson-Neyman technique revealed that, within a specific region (extraversion values above 21.93 and/or neuroticism values below 23.78), mindfulness was significantly associated with the global PSQI score; beyond the value regions, the significant association was lost. It suggests that mindfulness might play a protective role against sleep disturbance only among certain oncology nurses. The findings are valuable for identifying those who are more vulnerable to sleep dysfunction and may aid in targeted intervention planning.